Correction: Photothermal Möbius aromatic metallapentalenofuran and its NIR-responsive copolymer. Issue 18 (1st May 2018) - Lu, Zhengyu; Cai, Yuanting; Wei, Yuanqing; Lin, Qin; Chen, Jiangxi; He, Xumin; Li, Shunhua; Wu, Weitai; Xia, Haiping
Abstract : Correction for 'Photothermal Möbius aromatic metallapentalenofuran and its NIR-responsive copolymer' by Zhengyu Lu et al., Polym. Chem., 2018, 9, 2092–2100.